Case report of lung hydatid cyst - Mohammad Emami ardestani; Elham Kalantari (Iranian South Medical Journal, 2015)
Pulmonary hydatid cyst caused by the larval stage of echinococus parasit manifests in a variety of features from asymptomatic to symptoms including chronic cough,pleuritis,chest pain and hemoptysis due to cyst rupture into bronchus.some radiologic paterns has been described for it.the case we present it here is an unusual case regarding its patern of pulmonary involvement radiologically.